Reflection and Amendment of China’s Nuclear Energy Policies and Laws with the Background of Global “Nuclear Relaunch” - Haifeng Deng; Zihuai Tang (Energies)
The design of a country’s nuclear energy development policy and legal system is crucial to the development of its nuclear energy industry, and thus also affects international issues such as climate change and energy green and low-carbon transformation. Under such a “Nuclear Relaunch” era that the world is experiencing, China’s nuclear power installed capacity has reached second in the world, and China’s nuclear energy policies and laws will have a significant impact on the development of civil nuclear energy worldwide. Therefore, it is crucial to reflect on the problems existing in China’s nuclear legal system and theoretical research and propose corresponding amendments based on the review of China’s existing nuclear energy policy and law and the comparison with the relevant system design of other countries. This paper first extracts the common clues of nuclear power development in the world through historical and comparative studies on the development of nuclear energy policies and laws in China and other countries in the world. Secondly, combined with relevant data such as the scale of China’s nuclear power industry, the number and focus of policies and laws, this paper comprehensively analyzes and points out the current practical difficulties faced by China’s nuclear energy policies and laws from an empirical perspective. Finally, in response to these practical difficulties, this paper will propose amendments such as promoting atomic energy legislation, improving the nuclear safety legal standard system and independent supervision system, and strengthening information disclosure in the field of nuclear energy.